Anxious Behavior of Adult CD1 Mice Perinatally Exposed to Low Concentrations of Ethanol Correlates With Morphological Changes in Cingulate Cortex and Amygdala - Madarnas, Catalina; Villalba, Nerina Mariel; Soriano, Delia; Brusco, Alicia (Frontiers in Behavioral Neuroscience, 2020)
Perinatal ethanol (EtOH) exposure is associated with high incidence of behavioral disorders such as depression and anxiety. The cerebral areas related with these consequences involve the corticolimbic system, in particular the prefrontal cortex, hippocampus, amygdala and cingulate cortex, although the latter has not been thoroughly studied yet. Different animal models of prenatal or perinatal EtOH exposure have reported morphofunctional alterations in the central nervous system which could explain behavioral disorders along life; these results focus on youth and adolescents and are still controversial. In the light of these inconclusive results, the aim of this work was to analyze adult behavior in CD1 mice perinatally exposed to low concentrations of EtOH (PEE) during gestation and lactation, and describe the morphology of the cingulate cortex and amygdala with a view to establishing structure/function/behavior correlations. Primiparous CD1 female mice were exposed to EtOH 6% v/v for 20 days previous to mating and continued drinking EtOH 6% v/v during pregnancy and lactation. After weaning, male pups were fed food and water ad libitum until 77 days of age, when behavioral and morphological studies were performed. Mouse behavior was analyzed through light-dark box and open field tests. Parameters related to anxious behavior and locomotor activity revealed anxiogenic behavior in PEE mice. After behavioral studies, mice were perfused and neurons, axons, serotonin transporter, 5HT, CB1 receptor and 5HT1A receptor were studied by immunofluorescence and immunohistochemistry in brain sections containing cingulate cortex and amygdala. Cingulate cortex and amygdala cytoarchitecture were preserved in adult PEE mice, although a smaller number of neurons was detected in the amygdala. Cingulate cortex axons demonstrated disorganized radial distribution and reduced area. Serotonergic and endocannabinoid systems, both involved in anxious behavior, showed differential expression. Serotonergic afferents were lower in both brain areas of PEE animals, while 5HT1AR expression was lower in the cingulate cortex and higher in the amygdala. The expression of CB1R was lower only in the amygdala. In sum, EtOH exposure during early brain development induces morphological changes in structures of the limbic system and its neuromodulation which persist into adulthood and may be responsible for anxious behavior.